Fifty shades darker - James, E. L. (James, E. L. Fifty shades trilogy, 2012)
Daunted by the singular sexual tastes and dark secrets of the beautiful, tormented young entrepreneur Christian Grey, Anastasia Steele has broken off their relationship to start a new career with a Seattle publishing house.